Evaluate Accessibility to Public Transport Stops In The City of Lattakia Using GIS - رستم اكرم; سلمان فاتن (Latakia University Journal -Engineering Sciences Series, 2021)
Public transportation is the main component of the transportation system, which greatly serves to alleviate the economic and environmental burdens resulting from the increase in the rate of use of private cars as a means of transportation, and since access to public transport is an important factor in evaluating the quality and efficiency of public transport system, it was necessary to search for evaluation methodologies appropriate for assessing accessibility to public transportation. This research provides an assessment of the accessibility of public transport stops based on a set of indicators that take into account the coverage area of the public transport stop in order to identify the situations that suffer from difficult access. This study was conducted on AL- Zera’ah bus-line in the city of Lattakia, where ArcGIS software was used to determine the ideal coverage area and the actual coverage area for public transport stops on this line. The results of the study showed that there are some stops that suffer from difficult access, and the study also showed that the Actual Stop Accessibility Index gives more accurate values in measuring accessibility than the Ideal Stop Accessibility Index, but it is not possible to use it to compare the accessibility of different public transport stops sites as the denominator for this indicator(the actual parking area coverage area) is not fixed, it changes with the location of the public transport stop and depends on the formation of the road network surrounding the stop.